49th AIAA/ASME/SAE/ASEE Joint Propulsion Conference 2013
DOI: 10.2514/6.2013-3852
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Characteristics on a Coaxial-Porous Injector

Abstract: A coaxial-porous injector concept for gas-liquid combustion is proposed as a means of improving the mixing performace of a conventional shear-coaxial injector. The coaxialporous injector discharges a gas jet in the normal direction of the center liquid core, and it is expected that the momentum transfer from the radial gas jet to the axial liquid jet occurs more efficiently than it does with a traditional shear-coaxial injector. To validate the effectiveness of this idea, the combustion performances between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The spray from the PRS injector spread wider than the SHR injector due to the radial momentum transfer to the center liquid jet, as observed in the previous cold flow study. 8,12 Although the cold flow spray tests were conducted in an atmospheric condition, the disintegration behavior was quite similar with that of the reactive spray. The disintegration and phase change patterns could be observed more clearly by converting the shadowgraph image to the density gradient magnitude image, as shown in Fig.…”
Section: B Spray Patterns: Shadowgraph and Density Gradient Magnitudmentioning
confidence: 96%
See 2 more Smart Citations
“…The spray from the PRS injector spread wider than the SHR injector due to the radial momentum transfer to the center liquid jet, as observed in the previous cold flow study. 8,12 Although the cold flow spray tests were conducted in an atmospheric condition, the disintegration behavior was quite similar with that of the reactive spray. The disintegration and phase change patterns could be observed more clearly by converting the shadowgraph image to the density gradient magnitude image, as shown in Fig.…”
Section: B Spray Patterns: Shadowgraph and Density Gradient Magnitudmentioning
confidence: 96%
“…8 The results revealed that the coaxial porous injector configuration showed higher c * efficiency particularly in the low O/F ratio (low momentum flux ratio) condition. Also, the cold flow spray patterns were visualized to find the reason for the difference in combustion performance of the two experimental injectors.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation